Sistem Informasi Pemesanan Produk Percetakan Berbasis Web pada CV. Page Grafika Banda Aceh - Jamaluddin; Hajriyanti, Rahmi; Bahruni (Computer Journal, 2023)
Printing Product Ordering Information System is one of the data processing activities at CV. Graphic Page, to get information on ordering printing products to be more focused and easy to obtain. In writing this study, the authors limited the problem only to the web-based Printing Product Ordering Information System on CV. Graphics Pages. The purpose of writing is to identify and design a web-based Printing Product Ordering Information System on CV. Graphics Pages. The collection of data needed in writing this report was obtained by two methods, namely literature studies related to library books and other scientific works, field studies by conducting interviews and direct observation of objects related to this research. Web-based Printing Product Ordering Information System at CV. Page Graphics is performed by one of the administrative staff and assisted by 2 (two) administrative staff in the warehouse sector to record and input product data. From the results of the study it can be concluded that the Information System for ordering web-based printing products at CV. Page Graphics has followed the procedure and uses a computer with the programming language PHP and MySQL as its database.